The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1063/1.117127
|View full text |Cite
|
Sign up to set email alerts
|

Electron paramagnetic resonance of erbium doped silicon

Abstract: Electron paramagnetic resonance measurements have been made on samples of float zone silicon, implanted with 10 15 Er/cm 2 . One sample was coimplanted with oxygen to give an impurity concentration of 10 20 O/cm 3 and 10 19 Er/cm 3 . In this coimplanted sample, sharp lines are observed which are identified as arising from a single spin 1/2 Er 3ϩ center having a g tensor exhibiting monoclinic C 1h symmetry. The principal g values and tilt angle are g 1 ϭ0.80, g 2 ϭ5.45, g 3 ϭ12.60, and ϭ2.6°. In the absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 20 publications
0
33
1
Order By: Relevance
“…It was reported that ESR lines from Er 3ϩ center with Er 2 O 3 structure were observed in a Si wafer implanted with Er and oxygen. 4 The ESR lines for the D center are observed in the same region of the magnetic field as the ESR lines observed in Si. It is known that Er 3ϩ ion occupies two different sites in Er 2 O 3 .…”
Section: D Centermentioning
confidence: 52%
See 1 more Smart Citation
“…It was reported that ESR lines from Er 3ϩ center with Er 2 O 3 structure were observed in a Si wafer implanted with Er and oxygen. 4 The ESR lines for the D center are observed in the same region of the magnetic field as the ESR lines observed in Si. It is known that Er 3ϩ ion occupies two different sites in Er 2 O 3 .…”
Section: D Centermentioning
confidence: 52%
“…Knowledge of the microscopic structures of the rare earth impurities in semiconductor hosts is very important for fabricating efficient injection-type light emitting devices. To understand the microscopic structures, the electron spin resonance ͑ESR͒ measurements, [1][2][3][4][5][6][7] the extended x-ray absorption fine structure ͑EXAFS͒ measurements, 8,9 and the Rutherford backscattering ͑RBS͒ channeling measurements [10][11][12][13] have been performed on Er-doped GaAs, Er-doped Si, and Yb-doped InP.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have reported a preliminary EPR study on Er-doped Si and indeed we have shown the presence of Er 3ϩ centers in Si. 19 In this paper we present the first detailed EPR study of Er complexes in Si implanted with Er together with either O or F. We show that the nature of the coimplanted ions as well as their concentrations and the postimplantation anneal treatments all affect the structure and/or the concentration of the Er complexes. The relationship between the EPR-active centers and the optically active centers is examined using high-resolution PL measurements.…”
Section: Introductionmentioning
confidence: 99%
“…At concentrations above the solubility limit, precipitation of Er into Er silicide will occur. Coimplantation with either O or F has been shown to help in suppressing precipitation and Er concentrations as high as of 1ϫ10 19 /cm 3 have been incorporated in a goodquality Si single crystal by ion implantation. 6,13 These beneficial effects have been attributed to modifications in the local environment of the Er atom through the formation of Er-impurity complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Other RBS and PL measurements indicate that when annealed at over 800°C, 80% of Er occupies substitutional sites with tetrahedral symmetry [12]. Electron paramagnetic resonance (EPR) spectra of Er and O coimplanted Si indicate two Er 3+ centers having monoclinic C 1h symmetry [13] and trigonal symmetry [14]. The emission channelling technique indicates that Er in FZ Si occupies tetrahedral interstitial sites [15], and first-principles calculations indicate that the lowest energy configuration of Er in Si is Er 3+ at a tetrahedral interstitial site [16].…”
Section: Introductionmentioning
confidence: 99%